PENINGKATAN MOTIVASI BELAJAR EKONOMI MATERI PENDAPATAN NASIONAL DENGAN MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MEDIA INTERAKTIF (ICT) - Haryati, Siti (Dinamika Pendidikan, 2013)
Studentsâ motivation to learn Economics especially at 10th Grade on the Unit of National Income in SMA N 1 Ungaran in the academic year of 2011/2012 was low. It was only 50% students who got score more than the minimum score (KKM). The research discussed about the effort to improve studentsâ learning achievement on the unit of National Income through interactive media (ITC) with talking stick learning model. The objective of the class action research was to improve studentsâ achievement on Economics on the unit of National income. The learning process was done in 2 cycles. Based on the result and discussion, pre-test assessment, 1st cycle test, and 2nd test cycle, the tests showed the increase. There were 16 students (50%) from 32 students who completed the competencies on the pre-test, then it increased to 25 students (78.13%) on the 1st cycle and finally all students (100%) completed the competencies on the 2nd cycle. Furthermore, studentsâ motivation based on the questionnaire showed that there were 84.39% students agreed and 15.61% disagreed on the 1st cycle. Then, it increased to 93.75% on the 2nd cycle. Whereas, the observation on the 1st cycle showed that there were less motivated students and after joining to the 2nd cycle, almost all students were more active so the study result increased.